Current research and future prospects of air pollutant and CO2 emission inventories in the iron and steel industry - Xin XU; Wanyue SHAN; Zheng ZHANG; Qing WANG; Xin BO (工程科学学报)
Emission Inventory serves as a valuable tool for effectively characterizing pollution profiles and greenhouse gas emissions in the study area, offering a robust scientific foundation for developing pollutant prevention and control measures and collaborative emission reduction strategies. Amid global efforts to promote green and low-carbon development, the iron and steel industry, one of the key industrial sectors, has drawn increasing attention for its CO2 and air pollutant emissions. The low-carbon transformation of this industry has become an inevitable trend. As low-carbon innovative technologies continue to develop and be implemented, emission inventories for the iron and steel industry are progressing toward greater precision and comprehensiveness. The emergence of new technologies, such as electric arc furnace steelmaking, hydrogen metallurgy, and carbon capture, utilization, and storage, offers innovative solutions for reducing carbon emissions while simultaneously increasing demands for more accurate emission inventories. Traditionally, emission inventories have relied on generalized emission factors for estimating emissions. However, the advancement of low-carbon technologies introduces greater diversity in emission sources and variations in emission characteristics, necessitating the development of more refined emission inventories. Therefore, research on air pollutants and CO2 emission inventories in the iron and steel industry is crucial. Drawing on extensive domestic and international literature, this study summarizes and organizes the development of emission inventories in this sector across four key dimensions: (1) accounting methods for air pollutants and greenhouse gases, with greenhouse gas accounting primarily focusing on CO2; (2) emissions at global, intercontinental, national, urban, and urban agglomeration scales; spatial distribution of inventories; (3) uncertainty analysis, along with identified limitations and (4) future prospects for improvements. This study highlights several critical issues in China’s iron and steel industry, including challenges related to the diversity and quality of emission inventory data, the construction of an unorganized emission accounting system, deficiencies in CO2 accounting systems and methodologies, challenges in characterizing component spectra of volatile organic compounds (VOCs) and particulate matter profiles for key processes, obstacles in developing detailed time series for steel enterprises using continuous emission monitoring system (CEMS), and concerns in the practical application of emission inventories. Future efforts should prioritize diversifying the types of emission inventory data in the steel industry and enhancing the collection and analysis of measured data to improve the accuracy of foundational data. In addition, establishing a comprehensive, unorganized emission accounting system and optimizing the CO2 accounting framework and methods are essential. Incorporating real-time CEMS monitoring data and integrating composition profiles of VOCs and particulate matter characteristics from key processes can remarkably enhance the resolution of emission inventories. Furthermore, expanding the applications of emission inventories, fostering interdisciplinary and international collaborations, and promoting green and low-carbon development in the iron and steel industry are vital for achieving the synergistic control of global air pollutants and greenhouse gas emissions.